MARO TRADITION IN BANYUMAS COMMUNITY - Rahmini Hadi (IBDA` : Jurnal Kajian Islam dan Budaya, 2020)
This article discusses the Maro tradition of Banyumas commu- nity, whose existence is endangered by the modernization. Maro is a tradition dealing with agriculture profit share between a landowner and the cultivators by dividing the harvest into two equal parts, half is for the landowner, and the other half is for the cultivator. Maro is commonly applied for dividing the net profit, i.e. the amount of harvest minus the expenses of plantation processes. This tradition enables the low social- economy class to survive as they get the fair benefit for their efforts. The data of this research were collected through interviewing the people en- gaged in the Maro tradition as well as literary studies from previous re- searches related to the topic. This research finds that maro tradition in Banyumas has been popular since the arrival of tarekat in this region. The lands owned by kyai were rented to the cultivators whose payment is given in the form of profit-sharing, called Maro. With such a system, the profit is shared fairly to the cultivators who have done a lot of effort in producing rice. This system meets Islamic values, which emphasize profit sharing based on efforts and work performances. The landowners give freedom to the cultivators, and the net harvest obtained is divided equally between the two parties. Maro system, which was carried out with an oral contract, is considered not to burden the cultivators because of the clear counting system and easy procedures. Social solidarity is also formed in this tradition, it employs people to help the planting and harvesting process, called sambatan.